STRENGTHENING AGILE GOVERNMENT IN IMPLEMENTATION OF THE COVID-19 VACCINATION POLICY IN KALIMANTAN ISLAND - Nurul Kharismawati Kamaludin; Dyah Mutiarin (Journal of Governance and Public Policy, 2023)
This study aims to determine the Strengthening of Agile Government in implementing Covid-19 Vaccination Policies: Studies in 5 Provinces on the Island of Kalimantan. This research is a qualitative case study designed to analyze the findings with four characteristics of agile government: responsiveness, strategic adaptation, focus on results, and management anticipates future problems. This study shows that the best responsiveness in East Kalimantan Province, the responsiveness of handling the Covid-19 vaccine is considered very agile, the responsiveness level is 25.00%. In contrast, the province that is still under its responsiveness is West Kalimantan Province with its responsiveness. 14,00% rate. Furthermore, the highest strategy adaptation is the Province of South Kalimantan and Central Kalimantan, 22.00%, both of which have the same percentage value. At the same time, the lowest percentage is in North Kalimantan Province, which is 16.00%. In addition to Focus on Results, the highest percentage of achievement results in West Kalimantan Province, which is 31.00%. At the same time, Central Kalimantan, East Kalimantan, and North Kalimantan Provinces have a low achievement rate of 15.00%. Then in the Management of Overcoming Future Problems, the highest percentage is the Province of West Kalimantan, which is 26.00%, and the Provinces of East Kalimantan and Central Kalimantan, which have a low yield of 15.00%. The five provinces have different strategies for dealing with vaccination.